'Hope you find your 'eureka' moment soon': a qualitative study of parents/carers' online discussions around allergy, allergy tests and eczema. Issue 11 (18th November 2018) - Halls, Amy; Nunes, Dale; Muller, Ingrid; Angier, Elizabeth; Grimshaw, Kate; Santer, Miriam
Abstract : Objectives: To explore understandings and concerns surrounding allergy, food intolerances and their potential impact on eczema among parents and carers of children with eczema who had posted messages in online forums. Methods: We conducted a scoping review for active UK-based discussion forums that did not require password/registration to view posts and identified two parenting discussion forums with high activity and frequent use. We used their internal search functions to identify and export discussion threads relating to allergy and allergy testing for eczema from 2011 to 2016. We carried out an inductive thematic analysis of the 120 exported discussion threads. Results: 246 pages of text were analysed. Analysis led to three main themes: (1) confusion over the language surrounding 'allergy' and 'intolerance'; (2) diverse beliefs about allergy testing in relation to eczema and (3) parents' frustrations with perceptions of health professionals as uninterested and unhelpful about allergy testing. Forum users were concerned about immediate and delayed-type allergies but showed confusion in how terms were used, as well as different approaches to testing. Parents sought experiences of others, seeking social support as well as practical guidance. Conclusions: The confusion around allergy-related terminology and its possible relationship with eczema means that it is essential healthcare professionals are able to signpost parents to accurate, accessible information. The lack of consistent information currently available means parents may use online discussion forums as an important source of information. This study suggests that the confused nature of discussions on these forums is inaccurate at best, and detrimental at worst.